Pseudocyst of the auricle : management options - Atul M Bage; Nutan N Bage; D Anand Karthikeyan; Vijayasundaram (Wolters Kluwer Medknow Publications, 2012)
Background & Aims: Pseudocyst of auricle otherwise called as auricular seromais a cystic swelling filled with serous fluid. It occurs spontaneously or following surgery or trauma. Successful treatment of seromas remain a challenge because this disease has a high propensity for recurrence. The aim was to study the role of triamcinolone in reducing recurrence of pseudocyst of the auricle. Materials and methods : A total of 50 patients with pseudocyst of auricle were randomized into two groups. They were followed up to a year for recurrence. The technique of intra-lesional injection of triamcinolone acetonide after aspirating the fluid was followed in one group as against aspiration and tight bandaging in another group. Results : Out of seroma patients who underwent aspiration and bandaging, 90.91% had recurrence as against only 25.64% recurrence in patients who underwent aspiration and Inj.Triamcinolone infiltration. Out of seroma patients who underwent aspiration and bandaging 54.55% had recurrence within 1 month of initial treatment and 27.27% of them had a second recurrence within 3 months. Conclusion : Intra- lesional injection of triamcinolone is a promising treatment option for management of auricular seroma. It prevents the recurrence also.